2020
DOI: 10.2147/ijn.s249751
|View full text |Cite
|
Sign up to set email alerts
|

<p>Topical Application of Exosomes Derived from Human Umbilical Cord Mesenchymal Stem Cells in Combination with Sponge Spicules for Treatment of Photoaging</p>

Abstract: The topical application of exosomes secreted by mesenchymal stem cells (MSC-Exos) on the skin is a very new and interesting topic in the medical field. In this study, we aimed to investigate whether marine sponge Haliclona sp. spicules (SHSs) could effectively enhance the skin delivery of human umbilical cord-derived MSC-Exos (hucMSC-Exos), and further evaluate the topical application of hucMSC-Exos combined with SHSs in rejuvenating photoaged mouse skin. Materials and Methods: SHSs were isolated from the expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 41 publications
0
55
0
5
Order By: Relevance
“…Intrathecal is the preferred route in neurodegenerative conditions such as Alzheimer's, Parkinson's, and Creutz-Feld Jakob's disease (98,99). Local aerosol sprays are used in the management of wounds and ulcers (107,108). For hair growth and rejuvenation in age-related therapies, this is the preferred route (108,109).…”
Section: Routes Of Delivery Of Exosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrathecal is the preferred route in neurodegenerative conditions such as Alzheimer's, Parkinson's, and Creutz-Feld Jakob's disease (98,99). Local aerosol sprays are used in the management of wounds and ulcers (107,108). For hair growth and rejuvenation in age-related therapies, this is the preferred route (108,109).…”
Section: Routes Of Delivery Of Exosomesmentioning
confidence: 99%
“…Local aerosol sprays are used in the management of wounds and ulcers (107,108). For hair growth and rejuvenation in age-related therapies, this is the preferred route (108,109). During the time of the coronavirus disease-2019 (COVID-19) pandemic, there have been interesting studies discussing the role of exosomal therapy as a promising therapeutic candidate (110).…”
Section: Routes Of Delivery Of Exosomesmentioning
confidence: 99%
“…The topical application of exosomes secreted by MSCs (MSC-Exos) on the skin is a very new and interesting topic in the medical field. Zhang et al [ 38 ] investigated whether marine sponge Haliclona sp. spicules (SHSs) could effectively enhance the skin delivery of human umbilical cord-derived MSC-Exos (hucMSC-Exos), and further evaluated the topical application of hucMSC-Exos combined with SHSs in rejuvenating photoaged mouse skin.…”
Section: The Effect Of Exosomes On Skin Photoagingmentioning
confidence: 99%
“…Interestingly, they also found decreased MMP-1 production, which works as a collagenase and encodes a secreted enzyme which breaks down the types I, II, and III interstitial collagens ( Tallant et al, 2010 ; Kim et al, 2017 ). Lastly, Zhang K. et al (2020) studied whether the marine sponge Haliclona sp. spicules (SHSs) could effectively enhance the skin delivery of exosomes from hUC-MSCs by evaluating its topical application in rejuvenating photoaged mouse skin.…”
Section: Exosomes and Oxidative Stress Photoaging And Rejuvenationmentioning
confidence: 99%
“…It was reported that the combination of exosomes and SHSs showed significant anti-photoaging effects in mice, including reducing microwrinkles, alleviating histopathological changes and promoting the expression of extracellular matrix constituents. Moreover, skin irritation tests on a guinea pig animal model showed slight irritation ( Zhang K. et al, 2020 ) ( Table 1 and Supplementary Table 3 ).…”
Section: Exosomes and Oxidative Stress Photoaging And Rejuvenationmentioning
confidence: 99%